Stability-Indicating Spectrophotometric Methods for Determination of Milnacipran HCl and Duloxetine HCl in Bulk Drug and Pharmaceutical Formulations - Maha F. Abdel Ghany; Omar Abdel-Aziz; Nermine V. Fares; Eman Wafik Eskander (Ain Shams University, 2019)
The present study describes accurate and sensitive stability-indicating spectrophotometric methods for the determination of Milnacipran HCl in presence of its acid, base degradates, and Duloxetine HCl in presence of its base degradates; including Dual-wavelength, Ratio difference, and Ratio derivative techniques. The developed methods were validated according to the International Conference on Harmonisation (ICH) guidelines. The recovery percentage of Milnacipran HCl and Duloxetine HCl were found to be in the ranges 99.42-100.42% and 100.17-100.3%, respectively. The low relative standard deviation of precision results confirms the suitability of the proposed methods for the estimation of the studied drugs in pure form, laboratory-prepared mixtures, and pharmaceutical formulations. Statistical comparison of the proposed methods with the reported methods revealed that there were no significant differences concerning the accuracy and precision of the adopted techniques. Validation studies demonstrated that the proposed methods are easy, specific, and rapid for the determination of Milnacipran HCl and Duloxetine HCl.